Features and motivators of emotionally expressive firesetters: the assessment of women in secure psychiatric settings. Issue 2 (19th August 2014) - Long, Clive; Dickens, Geoffrey; Dolley, Olga
Abstract : Purpose: To assess the antecedent behaviours and consequences of firesetting for women in a secure psychiatric setting along with treatment engagement factors. To explore predictions made about emotionally expressive subtype firesetters by the multi-trajectory theory of adult firesetting (M-TTAF). Design/methodology/approach: Seventy five individual firesetting episodes involving 25 female multiple fire setters were assessed using the St Andrew's Fire and Arson Risk Instrument (SAFARI). Assessments were made of treatment readiness, firesetting related self efficacy, insight and barriers to change. Findings: Findings support the relationship between recidivist firesetting and the psychological features of psychosis, personality disorder and substance misuse. The reported association of firesetting with suicidal thoughts, depression, interpersonal problems, anger/revenge motivation, and lack of planning supports the view that behaviour is used to manage distressing life experience and as a "cry for help". However, in a quarter of incidents there was an intention to harm others and evidence of premeditation in twelve percent. A small but significant minority lacked insight into their behaviour, were not ready for treatment and had low firesetting related self efficacy. Predictions made by the M-TTAF about likely clinical features and motivators of emotionally expressive firesetters were largely supported. Originality/value: St Andrew's Fire Assessment & Risk Assessment Inventory (SAFARI; Long, Banyard, Fulton & Hollin, in press a) has been developed to assist in the assessment of firesetting among women in secure psychiatric settings. SAFARI provides a functional analysis of firesetting behaviour which, in combination with factors such as treatment readiness, leads to an individually tailored treatment plan. The aim of the current study is to describe the results of an assessment of a sample of recidivist women fire setters in a secure psychiatric setting using SAFARI that is based on both contemporary patient interview and historical data.